Solar H evolution in water with modified diketopyrrolopyrrole dyes immobilised on molecular Co and Ni catalyst-TiO hybrids - Warnan,J; Willkomm,J; Ng,J; Godin,RP; Prantl,S; Durrant,J; Reisner,E (Chemical Science, 2017)
A series of diketopyrrolopyrrole (DPP) dyes with a terminal phosphonic acid group for attachment to metal oxide surfaces were synthesised and the effect of side chain modification on their properties investigated. The organic photosensitisers feature strong visible light absorption (λ = 400 to 575 nm) and electrochemical and fluorescence studies revealed that the excited state of all dyes provides sufficient driving force for electron injection into the TiO2 conduction band. The performance of the DPP chromophores attached to TiO2 nanoparticles for photocatalytic H2 evolution with co-immobilised molecular Co and Ni catalysts was subsequently studied, resulting in solar fuel generation with a dye-sensitised semiconductor nanoparticle system suspended in water without precious metal components. The performance of the DPP dyes in photocatalysis did not only depend on electronic parameters, but also on properties of the side chain such as polarity, steric hinderance and hydrophobicity as well as the specific experimental conditions and the nature of the sacrificial electron donor. In an aqueous pH 4.5 ascorbic acid solution with a phosphonated DuBois-type Ni catalyst, a DPP-based turnover number (TONDPP) of up to 205 was obtained during UV-free simulated solar light irradiation (100 mW cm−2, AM 1.5G, λ > 420 nm) after 1 day. DPP-sensitised TiO2 nanoparticles were also successfully used in combination with a hydrogenase or platinum instead of the synthetic H2 evolution catalysts and the platinum-based system achieved a TONDPP of up to 2660, which significantly outperforms an analogous system using a phosphonated Ru tris(bipyridine) dye (TONRu = 431). Finally, transient absorption spectroscopy was performed to study interfacial recombination and dye regeneration kinetics revealing that the different performances of the DPP dyes are most likely dictated by the different regeneration efficiencies of the oxidised chromophores.